Perlindungan Hukum Terhadap Pekerja Dengan Perjanjian Kerja Waktu Tertentu Yang Terkena Pemutusan Hubungan Kerja (Studi Putusan Nomor 20/Pdt.Sus-PHI/2024/PN Sby dan Nomor 927 K/Pdt.Sus-PHI/2024) - Felicia Natasha Dagali; Agus Prihartono; Dede Agus (Indonesian Journal Publisher, 2025)
Termination of employment of workers under Fixed-Term Employment Agreements (PKWT) remains a significant issue, particularly when employers terminate contracts verbally and without adhering to legal procedures, creating uncertainty and neglect of workers’ rights. This study identifies two problems: the form of legal protection granted to PKWT workers who are terminated early, and judicial considerations in resolving such disputes as reflected in Decisions Number 20/Pdt.Sus-PHI/2024/PN Sby and 927 K/Pdt.Sus-PHI/2024. Using a normative juridical method with statutory, conceptual, and case approaches, the research analyzes labor regulations, legal doctrines, and relevant court judgments. The findings show that PKWT workers terminated before the contract’s expiration are entitled to compensation and damages under Article 62 of the Manpower Act and Government Regulation Number 35 of 2021. Verbal termination is deemed procedurally defective because it omits mandatory written notification. Both the first-instance court and the Supreme Court held that the employer lacked a lawful basis for termination and consequently must provide full compensation. These decisions reinforce legal certainty and highlight that employers may not end PKWT contracts unilaterally without legitimate grounds and proper procedures. The study concludes that strong legal protection is essential to prevent arbitrary termination and ensure the fulfillment of workers’ rights.